The anatomy of collaboration in international development practice: comparative insights from Nigeria and Ghana. Issue 4 (19th May 2017) - Schmid, Jon; Pathak, Rahul
ABSTRACT: Collaborative project implementation approaches are common in international development practice. This article uses a mixed-methods research design to examine the dynamics of North–South collaboration in a development setting. It studies election-monitoring campaigns in Nigeria and Ghana that involved cross-sector collaborations between several organisations. A conceptual model of cross-sector collaboration is proposed, which is then validated against two cases. Results show that while existing approaches to conceptualising collaboration provide significant insight into the empirical cases, additional factors such as resource constraints and power hierarchies should be considered when studying development collaboration in a North–South context.